KOMUNIKASI INTERPERSONAL PADA PROSES PENDIDIKAN POLITIK PEMILIH PEMULA - Affiyah Tri Yuni Sari; Aissyah Dwi Fitriyani; Martriana Ponimin Said (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2019)
Political education is one of the important factors in determining the attitude of a voter in the conduct of elections. Beginner voters with low levels of political education tend to have voices that are still floating or called swing-voters. If it is not able to be convinced, the swing-voter can become a golput, but if it can be convinced, the swing-voter can be an additional vote for a candidate or party in the final result of the vote count. The phenomenon of political apathy can be reduced by providing political education to beginner voters, one of the methods is through interpersonal communication. The exchange of values ??that form the basis of interpersonal communication can also occur in the family. This study aims to determine how the role of interpersonal communication in the process of early voter political education. Using the interpretative paradigm and descriptive qualitative research methods, by conducting observations, interviews and documentation studies. The unit of analysis under study is individuals, namely beginner voters at Pramuka Island, Thousand Islands, DKI Jakarta Province. The results of the study show that the role of interpersonal communication in the process of political voter education at Pramuka Island is to conduct discussions, exchange information about politics, and conduct political socialization, this will affect the process of political voter education and political participation in the 2019 Election. Keywords: interpersonal communication; political education; beginner voters; general election